Innovation in Learning Media Based on the Related Word Mnemonic Method to Improve Javanese Script Comprehension in Fourth Grade MI Students - Sutrisno Condro Apriyanto; Beti Istanti Suwandayani; Agus Tinus (MIMBAR PGSD Undiksha, 2026)
Learning Javanese script remains Javanese script learning remains challenging because its abstract and complex forms and sounds are difficult for students to understand and remember. Limited instructional variety further reduces learning motivation and achievement.This study aimed to develop and evaluate the validity, practicality, and effectiveness of learning media based on the related-word mnemonic method to improve students' understanding of Javanese script. A Research and Development (R&D) approach using the ADDIE model was employed. The effectiveness of the developed media was examined through a quasi-experimental study with a non-equivalent control group design involving 44 fourth-grade students, comprising 22 students in the experimental group and 22 in the control group. Data were collected using expert validation questionnaires, user response questionnaires, and pre-test and post-test achievement tests, and analyzed using descriptive and inferential statistics. The findings indicate that the developed media was highly valid based on expert evaluation, highly practical according to teachers and students, and effective in improving Javanese script comprehension compared with conventional instruction. The experimental group achieved a moderate increase in learning outcomes, whereas the control group showed a low increase. These findings demonstrate that visual associations through the mnemonic method can reduce students’ cognitive load when understanding complex symbolic materials. The developed media can serve as an effective learning alternative for improving Javanese script literacy while supporting cultural preservation through more meaningful learning.